PENGARUH STRATEGI PROMOSI, DAYA TARIK WISATA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERKUNJUNG YANG BERDAMPAK KEPADA KEPUASAN WISATAWAN DI KOTA PANGKALPINANG - Muhammad Yunus S; Wargianto Wargianto; Erwin Mashud (LPPM STIE PERTIBA Pangkalpinang, 2019)
This study aims to examine the effect of promotional strategies, tourist attraction and service quality on visiting decisions and their impact on tourist satisfaction. The method in this study uses a survey and questionnaire method to several tourists visiting several tourist attractions in the city of Pangkalpinang. This study uses a quantitative analysis of primary data from field surveys. Respondents in this study amounted to 100 people. The results of the study concluded that there are influences on the variable of promotional strategies, tourist attraction and service quality on visiting decisions. The service quality variable is still less influential on tourist visiting decisions compared to the other two variables, so it is necessary to consider again how the quality of services provided to tourists in order to provide greater influence on the satisfaction of the tourists. The results of this study are expected to add insight and government policy to provide comfort to the tourists who visit. For future research, it is hoped that it will need to add other independent variables and add dimensions of each variable in order to add deeper knowledge